Rainfall characteristics determine respiration rate of biological soil crusts in drylands - Yang Zhao (Elsevier, 2021)
Altering precipitation regimes are of particular concern in drylands, where isolated rainfall events often drive ecosystem structure and function. This study aims to explore the effects of varying individual rainfall amount on the release of CO2 by biological soil crusts (biocrusts), which are dominant biotic components and play key roles in drylands, in different climate zones. For a field experiment, we sourced algal crust (early succession) and moss crust (later succession) from sites across the main arid and semi-arid regions of northern China along a precipitation gradient ranging from 180 mm in Tengger Desert to 390 mm in Mu Us Sandland. Then we measured the post rainfall CO2 release rates in response to five rainfall magnitudes (0–2, 2–5, 5–10, 10–20, >20 mm individual rainfall amount) over two years (2011–2012) using a Li-6400-09 Soil Chamber in a uniform background environment. To evaluate the effect of a rainfall amount, a coefficient of variation was calculated the C release of both biocrust types from each location (CV) and among different locations (CVLocations). The results showed that algal and moss crusts among different locations had higher amounts of C release after larger rainfall events, compared to small events. However, CV of both biocrust types from each location was lower after larger rainfall events. The CVLocations of algal and moss crusts showed contrary tendencies after rainfall events of >20 mm. These results imply that an increase in small-sized rainfall events (<5 mm) will lead to an increase in C release from biocrusts, but an increase in larger rainfall events (>20 mm) may lead to less variation in C release from algal crust-dominated regions and to increasing heterogeneity in C release from moss crust-dominated regions. This indicates that C-release amount from biocrust-covered regions may be easily changed by altering the number of individual rainfall events, even if the total annual rainfall amount stays the same. Further, how biocrusts in different successional stages respond to changes in rainfall regimes will be an important determinant of future C release patterns in drylands. These changes may even result in changing the way biocrusts contribute to the function of desert ecosystems. The current analyses also have important implications regarding changes in rainfall regimes that in turn change C release patterns in biocrust-covered regions.